Studi Unsur Tanah Jarang REE di Bagian Barat Bukit Sambung Giri Kecamatan Merawang Kabupaten Bangka - Mardiah Mardiah; Irvani Irvani (PROMINE, 2018)
as long as years. The other mineral associated tin ore mineral very potensial mineral in Bangka Islandis rare earth element REE. They are the future prospect mineral resources, and how in the featuretime this potential must have a high economic value. REE potential not yet explored and exploited welluntil now days in Bangka Island, and was left abundant in ex-mining area. They carried out from thetin ore mining and become mine waste or tailing and then through the stream flows to be suspensionor bed load sediment. The aim of this study is to identify the present rare earth based on surfaceoutcrop samples as vein and rock and to understanding their spatial distribution in The west part ofSambung Giri Hill Merawang District Bangka Regency. Primary data collection of outcrop of rockand vein in Sambung Giri Hill. Geochemical sediments analysis just for identification insemiquantitative the presence of rare earth elements Ce, La, Nd, Sm and Y. Rare earth element ofcerium (Ce), Nd and Sm just ancent in some small sample, but for Lantanum (La) and yittrium (Y)almost presence at all shallow surface veint rock. The spatial distribution of rare earth Ce, La, Nd, Smand Y show heterogeneity in laterally.